Janasangjog O Prakashana - Qader, Mirza Tarequl (editor) (Dhaka : Bangladesh Institute of Communication Studies and Public Relations, 2002)
Political Sc. and Public Admin
06\19\03
Keywords: Social Relation; Public Information; Published Documents; Intrnational Relations